Studies on bone enzymes. The assay of acid hydrolases and other enzymes in bone tissue - Vaes, G. (1965)
1. Nine acid hydrolases, cytochrome oxidase, alkaline phenylphosphatase and catalase were demonstrated in 0·25m-sucrose homogenates of newborn-rat calvaria. The acid hydrolases were: acid phenylphosphatase, acid β-glycerophosphatase, β-glucuronidase, β-N-acetylglucosaminidase (β-N-acetylaminodeoxyglucosidase), acid ribonuclease and acid deoxyribonuclease, showing optimum activity at about pH5; cathepsin, β-galactosidase and hyaluronidase, with optimum activity at about pH3·6. 2. The main kinetic characters of these enzymes have been studied and methods for their quantitative assay have been worked out. The activities present in bone are given and compared with those found in liver. 3. Acid-phosphatase activity was assayed with phenyl phosphate and β-glycerophosphate as substrates: activities with these two substrates appeared to be due to two different enzymes. Acid phenylphosphatase is particularly labile and is readily inactivated by various physical or chemical agents.